Expedient Copper-Free One-Pot Alkynylation–Cyclization Sequence for the Preparation of 2-Substituted 7-Azaindoles - Lessing, Timo; Sterzenbach, Fabian; Müller, Thomas J. J. (Synlett, 2015)
2-Substituted 7-azaindoles are rapidly and efficiently prepared in a one-pot copper-free alkynylation–cyclization sequence starting from 2-aminopyridyl halides and terminal alkynes. Most importantly the amino nitrogen atom neither requires activation nor protection throughout the sequence.
Keywords: 7-azaindoles; heterocycles; alkynylation; cyclization; one-pot reaction